Criminal Law Means for Counteraction to Corruption in Ukraine and Poland: Similar and Distinctive Features - Franchuk, Vasyl (Magyar Rendészet, 2023)
During the scientific research of any criminal-legal phenomenon or process, it is considered necessary to conduct an analysis of the origin of this phenomenon in a foreign country. This provides an opportunity not only to grasp the essence and understand the content of the subject of research, but also to develop effective countermeasures and borrow foreign experience. This becomes especially important in matters of combating corruption, when the criminal acts of officials reach not only domestic, but also international scales. Scientists’ positions, as well as the provisions of the current legislation in Ukraine and the Republic of Poland concerning the definition of the criminal law provisions for liability for corruption offenses are being researched, which is made on the relevant differences regarding the legislative enactment of the concept of “corruption” and its definition in the criminal law theory. Accordingly, a comparative approach to the methods of legislative consolidation of anti-corruption provides an opportunity to understand the social conditioning of the emergence of this phenomenon. Taking into account the integration processes in all spheres of life activity of society, the difference in the method of normative consolidation of actions forming such a phenomenon as corruption was revealed. This, in turn, not only indicates different forms of legislative fixation of the concept of the phenomenon, but also causes difficulties in the exchange of law enforcement practice, which causes a number of problems for both the relevant law enforcement agencies and ordinary citizens. A clear division and distinction between provisions on liability for corruption and corruption-related offenses was revealed. Taking into account the position of the domestic criminal law doctrine, the analysis of the current Polish legislation provided an opportunity to formulate real options for borrowing foreign experience to solve the specified problems.